Industrial application of membrane distillation technology using palm oil mill effluent in Malaysia. (2022) - Muhamad, N.A.S.; Hanoin, M.A.H.M.; Mokhtar, N.M.; Lau, W.J.; Jaafar, J.
Abstract: The palm oil industry plays a vital role in the nation's economy. Regardless of the high revenue generated, the main problem in the palm oil industry is its substantial amount of wastes including empty fruit bunches, oil palm trunks and in particular palm oil mill effluent (POME) which can be harmful to the environment if discharged without being treated. The objective of this work is to introduce advanced wastewater treatment technology, which is membrane distillation (MD) technology for the effluent treatment system. PVDF hollow fibre membranes were fabricated via wet spinning technique and characterized using Scanning Electron Microscope (SEM) and contact angle goniometer. The fabricated membranes were then tested in direct contact membrane distillation (DCMD) system using anaerobic POME as the feed solution. The effluent was analyzed before and after treatment with DCMD. The parameters included biological oxygen demand (BOD), chemical oxygen demand (COD), ammonia nitrogen (AN), nitrate-nitrogen (NN), total suspended solids (TSS), total dissolved solids (TDS), colour and turbidity. A preliminary test was carried out using distilled water before continuing with anaerobic POME as a feed solution. The average permeate flux obtained by the PVDF membrane is 2.509 kg/m 2 .hr with slight flux decline that is probably due to the attachment of biological compounds on the membrane pores. It was found that at least 90% rejection was obtained for almost all water quality parameters tested with the values were all lower than that of the standard set by the local authority. In a conclusion, it can be said that MD demonstrated excellent performance in treating palm oil wastewater to produce water of high quality. [copyright information to be updated in production process]